The Princely Fathom. Uniformization of Measures and State Making in Wallachia, 1775-1831 - OLARU, Vasile Mihai (Studia Universitatis Babeș-Bolyai Historia, 2015)
This article discusses the relationship between the uniformization of measures and the transformation of the state in Wallachia from 1775 to 1831 by focusing on the fathom (stânjen), a measure of length used before the introduction of the metric system. The extant Romanian historiography of weights and measure tended to consider early modern measures as standards easy to convert in the metric system. To the contrary, my article shows that that consistent attempts made by the central power – the princedom – to define and control the measures can be documented consistently only from the last quarter of the 18th century on. Triggered by the dissolution of communal property and the incipient commodification of land, this process of standardization contributed to the bureaucratisation of the state apparatus and to the constitution of the state as an impersonal entity. Rezumat: Stânjenul domnesc. Uniformizarea măsurilor şi constituirea Ţării Româneşti, 1775-1831. Articolul de faţă discută relaţia dintre uniformizarea măsurilor şi transformarea statului în Ţara Românească din perioada 1775-1831, concentrându-se asupra stânjenului, o măsură de lungime folosită înainte de introducerea sistemului metric. Istoriografia metrologică românească a tratat măsurile premoderne ca standarde, uşor de convertit în sistemul metric. Articolul meu arată în schimb că încercările coerente ale puterii centrale – domnia – de a defini şi controla măsurile pot fi documentate doar din ultimul sfert al veacului al XVIII-lea. Provocat de disoluţia stăpânirilor obşteşti şi de comodificarea incipientă a pământului, acest proces a contribuit la birocratizarea aparatului de stat şi la constituirea statului ca entitate impersonală. Cuvinte cheie: stânjen, standardizare, Ţara Românească, perioada fanariotă, stat, ideea de stat, birocratizare.